Intermittent Hypoxia and Hypercapnia Alter Diurnal Rhythms of Luminal Gut Microbiome and Metabolome - Celeste Allaband (American Society for Microbiology, 2021)
People with obstructive sleep apnea, identified by loud snoring and breathing irregularly while sleeping, are at a higher risk of high blood pressure, type 2 diabetes, cardiac arrhythmias, stroke, and sudden cardiac death. We wanted to understand whether the gut microbiome changes induced by obstructive sleep apnea could potentially explain some of these medical problems.